Tracer study as an effort to improve higher islamic education quality and relevance - Uswatun Khasanah (IAIN Salatiga, 2019)
This study identifies the profile of alumni and determines their absorption in the employment; describe their assessment of the organization and quality of services; and describes user ratings of alumni performance. This research includes a qualitative descriptive through a survey approach which includes stages: the development of concepts and instruments; data collection; data analysis and reporting. The subjects of this study were alumni of FUAD IAIN Pekalongan (graduated in 2013-2016). The number of respondents was 88 alumni and 14 alumni users. Primary data were obtained through an online structured questionnaire through Google forms, POS and direct dissemination. Data collection was conducted in May-August 2018. The results are: (1) Alumni profiles have high absorption, i.e. 47% of respondents in working positions, 21% of entrepreneurs, 16% of workers and entrepreneurs and 16% of not working/continuing their studies; (2) Alumni assessment of the organization and quality of services is “good”, but there is still a need to improve aspects of facilities and infrastructure; (3) Alumni users judge the performance of alumni in the “good” category. The alumni competence in terms of aspects of integrity; professionalism; use of information technology, communication; teamwork; and self-development is “good”.